Navegar lendo, ler navegando -: Aspectos do Letramento Digital e da Leitura de Jornais - Ana Elisa Ferreira Ribeiro (2008)
Based upon the concepts of literacy, digital literacy and mosaic media, supported by Chartier's concept of hypertext and by Coscarelli's hypertextual theory of reading, this work discusses the relationship established by low level literacy readers with the reading of printed and digital newspapers. At first, this case study was carried out with 144 first semester undergraduates of a nursing course at a private school of Belo Horizonte . From questionnaire-generated reading profiles, a group of 23 students was selected to make tests on navigation and on reading. Printed and digital platforms of Estado de Minas and O tempo newspapers were selected. The subjects were divided into three groups: printed platform readers, digital platform readers and newspaper non-readers. The selected newspapers were analyzed concerning their usability. Readers were given navigation tasks to perform. Subjects had to answer questions, which were proposed in accordance with Saeb exam reading abilities matrix. The generated data show great variation in readers' behavior when dealing with mosaic media. And this was not dependent on whether printed or digital the platform was. Thus, good navigators may be poor readers and good readers may be poor navigators. It seems that the relationship between knowing how to manage the reading object and reading abilities is indirect and non-proportional. So, it was possible to conclude that reading newspapers depends upon the development of many other abilities, independently of the reading platform; that reading is built up from a complex superposition of abilities, and that most of them do not receive adequate attention from Linguistics and are not contemplated in the SAEB exam reading abilities matrix. Might this research contribute to a serious discussion on the relevance of reading and of teaching how to read, a teaches' attribution that gets more complex each day.